3-Step Charrette: A Framework for Teaching Students to Solve Complex Problems in a Real-World Environment. (March 2021) - Bodine, Paul Arthur; Mothapo, Natasha Palesa; Reardon, Karen
The 3-Step Charrette problem-solving methodology turns the classroom into a consulting firm. It trains participants to solve complex, real-world problems cooperatively and systematically. Participants identify needed information and perform several research cycles in teams to gain knowledge to examine the root causes of a presented problem. Participants then re-form into different groups to find solutions, ultimately consolidating their chosen solutions into a plan of action. The jigsaw transposition from research teams to solving groups ensures that participants acquire needed expertise and properly characterize the problem before attempts to fashion solutions even begin. As participants follow the procedure, the instructor guides them using in-stream debriefing. Designed for use with a live client, this experiential exercise is useful for capstone, strategy, consulting, design thinking, and business architecture courses.